UNESCO and the Ley General de Educación: the influence of International Organizations arround educational modernization on the Francoism - González-Delgado, Mariano; Groves, Tamar (Historia y Memoria de la Educación, 2021)
This article analyzes the influence that the educational ideas proposed by UNESCO had on the development of the General Education Act (LGE) of 1970. More specifically, it attempts to establish the impact that this international organization had on the origin and development of the LGE during the Franco regime. To do so, the first part of the article studies the beginnings of UNESCO in Spain and how the educational conception that would give rise to one of the most important educational reforms of contemporary Spain was developed. In the second part, we examine the recommendations given by the «International Advisory Committee for the Reform of Education in Spain» regarding the debate generated by the Libro Blanco (White Paper). In the third part of the article we look at the Committe’s direct impact and the way its assessments guided the development of the LGE in its first years. This work aims to demonstrate that the LGE can be better understood as a reform born under the recommendations of UNESCO regarding the educational context originated within the framework of the Cold War and the Modernization Theory.